2022
DOI: 10.3390/jof8090890
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Pythium aristosporum Oomycete—A Novel Pathogen Causing Rice Seedling Blight in China

Abstract: Rice seedling blight is a globally occurring seedling disease caused by multiple pathogens. It is currently the most common disease affecting rice production in northeast China; hence, determining the causal agents, including its biological characteristics, host range, and fungicide efficacy is vital for its effective management. The present study obtained 45 pathogenic isolates from diseased rice seedlings in Suihua, Heilongjiang Province, China. Of these, five pathogens were identified based on their morphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…Negative results were observed in 16 samples, particularly in lettuce and rice. These results may be attributed to the potential infection of the symptomatic seedlings by fungi or other oomycetes [47][48][49] or the possibility of inadequate detection of root samples. The former suggests the necessity of implementing a comprehensive plant disease diagnosis system that effectively encompasses all major pathogens of the plant.…”
Section: Discussionmentioning
confidence: 99%
“…Negative results were observed in 16 samples, particularly in lettuce and rice. These results may be attributed to the potential infection of the symptomatic seedlings by fungi or other oomycetes [47][48][49] or the possibility of inadequate detection of root samples. The former suggests the necessity of implementing a comprehensive plant disease diagnosis system that effectively encompasses all major pathogens of the plant.…”
Section: Discussionmentioning
confidence: 99%
“…[15], Burkholderia plantarii [16,17], Cochliobolus carbonum [18], Marasmius graminum [19], F. redolens [20], Enterobacter asburiae [21], Pantoea ananatis [21], Rhizoctonia solani [10], Fusarium spp. [10], Sclerotium rolfsii [10], Marasmius graminum [10], and Pythium aristosporum [22]. However, F. oxysporum remains the dominant pathogen causing RSB in the northeastern rice-planting areas of China [4,23].…”
Section: Introductionmentioning
confidence: 99%
“…Research has demonstrated that bakanae disease is caused by sever seed-borne Fusarium species, with Fusarium fujikuroi, which is a member of the Gibberella fujikuroi species complex, being the main contributor ( Amoah et al, 1995 ; Desjardins et al, 2000 ; Wulff et al, 2010 ). Seedling rot disease is caused by various seed-borne and soil-borne fungal pathogens, including Curvularia lunata , Fusarium oxysporum , and Rhizoctonia solani ( Verma et al, 2018 ; Song et al, 2021 ; Liu et al, 2022 ). Seedling rot disease influences the seeds and seedlings of rice plants, with discernible disease symptoms typically emerging shortly after seed sowing ( Limtong et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%